Zygmunt Hübner - Ludzie cesarza - Wołodźko, Jerzy W. (1958- ).; Teatr Wybrzeże (Gdańsk). (Gdańsk : Teatr Wybrzeże, 1987)
Plakat teatralny.
Keywords: Teatr Wybrzeże (Gdańsk) -- plakaty; Plakaty -- 1945-1990.